2020
DOI: 10.46961/jip.v8i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Student Satisfaction in Usinge-Learning Media During the Corona Pandemicperiod

Abstract: The Corona pandemic has spread almost everywhere in the world. Indonesia became one of the affected countries. The education sector became one of the affected sectors and changed the learning process, which was initially dominated by conventional learning into E-Learning based learning. This sudden change makes all components of learning, especially teachers and instructors, have to adapt to use the facilities available. However, this sudden change inevitably creates obstacles to the achievement of learning ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…These results prove that hypothesis 5 and hypothesis 8. That result also support several previous studies (Bartley & Golek, 2004;El-Gohary, 2012;Gaffar & Septyandi, 2020). In this study also found that hypothesis 2 was rejected.…”
Section: Measurement Modelsupporting
confidence: 93%
See 4 more Smart Citations
“…These results prove that hypothesis 5 and hypothesis 8. That result also support several previous studies (Bartley & Golek, 2004;El-Gohary, 2012;Gaffar & Septyandi, 2020). In this study also found that hypothesis 2 was rejected.…”
Section: Measurement Modelsupporting
confidence: 93%
“…These results prove that hypothesis 9 and hypothesis 10 are proven. This also confirms that the results of previous studies are supported (Boateng et al, 2016;Gaffar & Septyandi, 2020;Ho et al, 2021;Singh et al, 2021). In addition, User satisfaction has a greater influence on Future Use Behavior than Attitude in this study.…”
Section: Measurement Modelsupporting
confidence: 92%
See 3 more Smart Citations